Calibration and Evaluation of Fixed and Mobile Relay-Based System Level Simulator. (18th July 2010) - Mumtaz, Shahid; Tu, Le Thanh; Saidul, Kazi; Gameiro, Atílio
Abstract : Future wireless communication systems are expected to provide more stable and higher data rate transmissions in the whole OFDMA networks, but the mobile stations (MSs) in the cell boundary experience poor spectral efficiency due to the path loss from the transmitting antenna and interference from adjacent cells. Therefore, satisfying QoS (Quality of Service) requirements of each MS at the cell boundary has been an important issue. To resolve this spectral efficiency problem at the cell boundary, deploying relay stations has been actively considered. As multihop/relay has complex interactions between the routing and medium access control decisions, the extent to which analytical expressions can be used to explore its benefits is limited. Consequently, simulations tend to be the preferred way of assessing the performance of relays. In this paper, we evaluate the performance of relay-assisted OFDMA networks by means of system level simulator (SLS). We consistently observed that the throughput is increased and the outage is decreased in the relay-assisted OFDMA network, which is converted to range extension without any capacity penalty, for the realistic range of values of the propagation and other system parameters investigated.